Biosorption of silver ions. - Toh, Guanhong. (2009)
Water pollution remains a serious environmental issue in the world today. This pollution is caused mainly by toxic heavy metals which are not biodegradable. They will accumulate in living organisms, causing various disorders and diseases. These toxic heavy metals must be removed before releasing back into the environment. Chitosan beads may be a suitable adsorbent. Chitosan is abundant in nature and they are low cost. Furthermore physical and chemical modifications are easily performed on chitosan to enhance its adsorption capability. The aim of this project is to investigate the feasibility of the adsorption of silver ions from aqueous solutions onto chitosan hydrogel beads. In this project, ECH-chitosan beads, BCD grafted chitosan beads and native chitosan hydrogel beads are tested for adsorption of silver ions. pH is varied across the range of 4 to 8. All three types of chitosan beads are able to adsorb silver ions. The adsorption isotherm data for adsorption of silver ions at various pH were fitted to Langmuir model and Freundlich model. It was found that both Langmuir equation and Freundlich equation showed high conformity with high R2 value for adsorption of silver ions onto native chitosan beads. The study showed native chitosan beads are the most effective in removal of silver ions from aqueous solution at a wide range of pH value. BCD grafted chitosan beads are the second most effective adsorbent followed by ECH-chitosan beads.